Formation of SiC by Vacuum Carbidization on Porous Silicon - M. V. Labanok; S. L. Prakopyeu; S. A. Zavatski; V. P. Bondarenko; P. I. Gaiduk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Planar-view TEM investigation revealed the formation of cubic silicon carbide layers on porous silicon by vacuum carbidization. The formation of cubic silicon layers in the form of a two-phase system was found. At the same time, the formed SiC layers on the mesoporous buffer layer are predominantly polycrystalline. Using the Rutherford backscattering method, it was found that the use of buffer layers of porous silicon makes it possible to obtain SiC layers of greater thickness than on a pure silicon substrate under similar conditions of vacuum carbidization. It is shown that an increase in the pore size in porous silicon layers leads to an increase in the thickness of the formed SiC layers. It has been shown by scanning electron microscopy that vacuum carbideization of porous silicon leads to formation of SiC grains in pores, partial overgrowth and sintering of pores. The dependence of the SiC grain size on the pore size was established.